The image of the multi-ethnic Habsburg Empire: From its dismissal in 1919 to its rediscovery for the European Union after 1989 - Prosser-Schell, Michael (Ethnographica et Folkloristica Carpathica, 2020)
This article delineates the image of the Habsburg Empire in the 20th century in order to analyse its current representation in historiography in the German language. Before the Great War, the comprehensive compendium „Die österreichisch-ungarische Monarchie in Wort und Bild“ (The Austrian-Hungarian Monarchy in Word and Image) presented the old Habsburg Empire in a very positive light. According to the compendium, the strong and progressive multi-ethnic state served as a model for the institution of the nation state. After the Great War, the Habsburg Empire appears as a weak, even non-functional state in historiography in the German language.  It is described as internally divided due to ethnic conflicts of interest. However, after 1990, following the publication of Claudio Magris’ renowned works, in particular his book on the river Danube, the image of the multi-ethnic Habsburg Empire as a culturally and politically dynamic actor has been reclaimed. After the enlargement of the European Union in 2004, the state’s multi-ethnic character has frequently been presented as a role model for European integration. To further illustrate this point, this article will examine the reasons for which Temeswar in the Banat was selected as European Capital of Culture.